Developmental Stability in Chickens Local to Warm Climatic Region 2. Variation in Blood Metabolites Due to Genetic Selection and Crossing - El-Gendy, Essam A.; El-Komy, Esteftah M.; El-Far, Ahmed A.; El-Gamry, Abdel Khalek A.; El-Mallah, Gamal M. (International Journal of Poultry Science, 2011)
An experiment was conducted to assess the variation in blood metabolic constituents in a local chicken line (CE1) selected five generations for increased 6-wk body weight. Also, line CE1 was reciprocally crossed with a Slow-Growing Commercial Broiler Strain (SGB). The local genetic control line (CRB) was used for genetic comparison. No significant differences were observed in the blood levels of total proteins, albumin, globulin and Albumin/Globulin (A/G) ratio among lines CE1 and CRB in both parental (P) and progeny (F1) generations. In P generation, total protein levels of 2.22 and 2.16 g/dl were obtained for lines CE1 and CRB and were significantly higher than 1.78 g/dl for strain SGB. Line CE1 had triglyceride level of 178.76 mg/dl which was significantly higher than 122.13 mg/dl for line CRB. Similar trend for the blood lipid metabolites were obtained in F1 generation. Sex variation in body weight although was obvious, the selection pressure on sex variation in metabolic activity was not existed. Significant heterosis estimates of -22.56 and 5.0% were obtained for the levels of total lipids and cholesterol. The heterosis estimates in the levels of total proteins, albumin, globulin, A/G ratio and triglycerides were -23.71, 9.94, -33.66, 14.97 and -3.63%, but lacked significance. Although heterosis estimates were mostly insignificant, they indicated that the metabolic activity could be drastically changed by crossing. The drastic change in the metabolic activity was too early to be noticeable in a short-term selection program. Selection pressure was more obvious in lipid metabolites, particularly triglycerides, than in protein metabolites. Highly moderate negative and significant correlation coefficient was obtained between globulin level and cholesterol level. The variable correlation relationships among blood metabolites and the insignificant correlations between blood metabolites and body weights did not reflect the continuous metabolic and tissue remodeling associated with growth. This could be due to the small size that characterizes local chickens of warm regions or the shortness of selection scheme that did not result in an obvious change in the metabolic activity.